2021
DOI: 10.21273/hortsci15771-21
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Quantification of Postharvest Losses of Apple Fruit Stored under Commercial Conditions

Abstract: The objectives of this study were to characterize and quantify postharvest losses of apples under commercial conditions in Santa Catarina state, Brazil. Two experiments were conducted using ‘Gala’ and ‘Fuji’ apples. The first experiment was to characterize and quantify the most important causes of loss of fruit treated or not treated with 1-methylcyclopropene (1-MCP) then held in controlled atmosphere (CA) storage. This experiment was conducted in commercial storage facilities from 2007 to 2010. In each year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Longer storage durations can increase the opportunity for postharvest infection and fungal development in fruit (KIM and XIAO, 2006;NERI et al, 2009). Decay occurrence in 'Luiza' fruit was lower than that found in 'Gala' and 'Fuji' apples stored in CA under commercial conditions (ARGENTA et al, 2021). These authors reported that losses caused by fungal decay during storage ranged from 8.4% to 17.6% for 'Gala' apples, depending on the year.…”
Section: Physiological and Quality Changes During Storage In Air And Camentioning
confidence: 90%
See 2 more Smart Citations
“…Longer storage durations can increase the opportunity for postharvest infection and fungal development in fruit (KIM and XIAO, 2006;NERI et al, 2009). Decay occurrence in 'Luiza' fruit was lower than that found in 'Gala' and 'Fuji' apples stored in CA under commercial conditions (ARGENTA et al, 2021). These authors reported that losses caused by fungal decay during storage ranged from 8.4% to 17.6% for 'Gala' apples, depending on the year.…”
Section: Physiological and Quality Changes During Storage In Air And Camentioning
confidence: 90%
“…1-MCP was effective in reducing fungal decay in air storage. Previous studies have reported that the effects of 1-MCP in reducing fungal decay is variable, which can reduce (CAMDELI et al, 2016), increase (JANISIEWICZ et al, 2003) or have no effect (ARGENTA et al, 2021).…”
Section: Monthmentioning
confidence: 98%
See 1 more Smart Citation
“…bras., Brasília, v.58, e03121, 2023 DOI: 10.1590/S1678-3921.pab2023.v58.03121 maturity, air-stored and not exposed to 1-MCP; this fact was associated to the faster reduction of TA during storage (Figure 3 B). Fungal decay is the main cause of apple losses after harvest, representing 60 to 80% of total losses of 'Gala' and 'Fuji' apples, respectively, under commercial conditions in Brazil (Argenta et al, 2021). The severity of fungal decay increased during storage in 'SCS417 Monalisa' apples which were highly affected by the harvest maturity, 1-MCP treatment, and storage atmosphere conditions (Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…Severity (2) Incidence (%) correlation between the incidence of fungal decay and flesh firmness may occur especially for early season cultivars, depending on the growing season (Argenta et al, 2021). A remarkable fact is that the CA storage conditions reduced the decay severity to a similar level as that of air storage with 1-MCP treatment.…”
Section: Monthmentioning
confidence: 99%